The Dawning Era of Nanoparticle Encapsulated Novel And Pioneering Formulations For Cancer Drug Delivery - Tiwari, Sourabh; Upadhyay, Dr. Ravi (Asian Journal of Pharmaceutical Research and Development, 2014)
Chemotherapy represents a core in the treatment of pancreatic cancer. Moreover, the early recognition and treatment of cancer remains a scientific bottleneck. There is an urgent need to develop new and innovative technologies that could help to delineate tumor margins, identify residual tumor cells and determine whether a tumor has been completely removed or not. Nanotechnology has witnessed significant progress in the past few decades, and its effect is widespread nowadays in every field. Nanoparticles can be modified in numerous ways to prolong circulation, enhance drug localization, increase drug efficacy, and potentially decrease chances of multidrug resistance by the use of nanotechnology. Recently, research in the field of cancer nanotechnology has made remarkable advances. This study was done to evaluate the efficacy of three nanoparticle encapsulated drugs over free drugs of the same commonly used regimens. Measures of anti-carcinogenic potential of the nano-engineered formulations were investigated using cultured carcinoma cells. Evaluation of apoptosis by Caspase-3 assay following 96 h treatment with SLN and native drugs delineated significant differences, establishing better potential efficacy of nano engineered drugs. These preliminary in vitro results suggest that SLN could be anticipated as alternative drug delivery system.